Productive efficiency of public and private solid waste logistics and its implications for waste management policy - Daisuke Ichinose (IATSS Research, 2013)
This paper measures the productive efficiency of municipal solid waste (MSW) logistics by applying data envelopment analysis (DEA) to cross-sectional data of prefectures in Japan. Either through public operations or by outsourcing to private waste collection operators, prefectural governments possess the fundamental authority over waste processing operations in Japan. Therefore, we estimate a multi-input multi-output production efficiency at the prefectural level via DEA, employing several different model settings. Our data classify the MSW into household solid waste (HSW) and business solid waste (BSW) collected by both private and public operators as separate outputs, while the numbers of trucks and workers used by private and public operators are used as inputs. The results consistently show that geographical characteristics, such as the number of inhabited remote islands, are relatively more dominant factors for determining inefficiency. While the implication that a minimum efficient scale is not achieved in these small islands is in line with the literature suggesting that waste logistics has increasing returns at the municipal level, our results indicate that waste collection efficiency in Japan is well described by CRS technology at the prefectural level. The results also show that prefectures with higher private-sector participation, measured in terms of HSW collection, are more efficient, whereas a higher private–labor ratio negatively affects efficiency. We also provide evidence that prefectures with inefficient MSW logistics have a higher tendency of suffering from the illegal dumping of industrial waste.